A parametric analysis of electroosmotic and magnetohydrodynamic flows with homogeneous-heterogeneous reactions between squeezing plates - Jan W.U.; Farooq M.; Shah R.A.; Khan A.; Jan R.; Ahmad I.; Idris S.A. (Springer Science and Business Media Deutschland GmbH, 2025)
The Poisson?Boltzmann equation characterizes the internal electric potential in electroosmotic and magnetohydrodynamic (MHD) processes, under the assumptions of thermodynamic equilibrium and negligible fluid flow effects. However, for significant convective ion transport, the Nernst?Planck equation is requisite. This study develops predictive models for electroosmotic and MHD flows between squeezing plates, where convective ion transport is minimal. The partial differential equations (PDEs) are transformed into ordinary differential equations (ODEs) using similarity transformations and solved analytically via the homotopy analysis method (HAM). The HAM results, validated against the numerical solver BVP4c, exhibit strong concordance. Various physical effects are elucidated through graphical and tabular representations, revealing that squeezing the plates reduces electroosmotic flow profiles while increasing the magnetic Reynolds number in both homogeneous and heterogeneous reactions. ? The Author(s), under exclusive licence to EDP Sciences, Springer-Verlag GmbH Germany, part of Springer Nature 2024.